Physiological interpretation of the slope during an isokinetic fatigue test - Bosquet, L.; Gouadec, K.; Berryman, N.; Duclos, C.; Gremeaux, V.; Croisier, J.-L. (International Journal of Sports Medicine, 2015)
To assess the relationship between selected measures (the slope and average performance) obtained during a high intensity isokinetic fatigue test of the knee (FAT) and relevant measures of anaerobic and aerobic capacities. 20 well-trained cyclists performed 3 randomly ordered sessions involving a FAT consisting in 30 reciprocal maximal concentric contractions of knee flexors and extensors at 180°/s, a maximal continuous graded exercise test (GXT), and a Wingate anaerobic test (WAnT). The slope calculated from peak torque (PT) and total work (TW) of knee extensors was highly associated to maximal PT (r=-0.86) and maximal TW (r=-0.87) measured during FAT, and moderately associated to peak power output measured during the WAnT (r=-0.64 to -0.71). Average PT and average TW were highly associated to maximal PT (r=0.93) and maximal TW (r=0.96), to mean power output measured during WAnT (r=0.83-0.90) and moderately associated to maximal oxygen uptake (0.58-0.67). In conclusion, the slope is mainly determined by maximal anaerobic power, while average performance is a composite measure depending on both aerobic and anaerobic energy systems according to proportions that are determined by the duration of the test.